Ovarian Teratoma Masquerading as a CSF Pseudocyst in a Female with a Ventriculoperitoneal Shunt. (24th June 2009) - Mislow, John M. K.; Slotkin, Jonathan R.; Proctor, Mark R.
Abstract : Background . In today's fast-paced and high-acuity emergency departments, clinicians are often compelled to triage cases so rapidly that a differential diagnosis consistent with the history and physical examination is not comprehensive. Case Report . This case report describes the unexpected finding of a cystic ovarian neoplasm in a young female with an abdominal mass and a ventriculoperitoneal shunt, initially diagnosed as a cerebrospinal fluid pseudocyst. We use this case to illustrate that the astute clinician must always synthesize a diagnosis from all data sources and not to rely on initial radiographic evaluations. Conclusions . This remarkable case demonstrates that all differential diagnoses must be entertained in order to rapidly and accurately diagnose a patient with a cystic abdominal mass.